A ANALYSIS OF LEGAL PROTECTION AND LABOR GENDER EQUALITY IN THE COAL MINING INDUSTRY PT. MUTIARA ETAM COAL, PALARAN DISTRICT, EAST KALIMANTAN - surya, Suryaningsi (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2024)
Regulations related to legal protection and gender equality in labor are crucial aspects, especially in industries dominated by male workers such as coal mining. This study aims to analyze legal protection for gender equality in the coal mining industry, with a case study on PT. MEC. The research method used is qualitative descriptive with a case study approach. This research involves company leaders and employees as research subjects, with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through the stages of collection, reduction, presentation, and drawing conclusions. The results of the study show that PT. The MEC complies with Law No. 13 of 2003 on Manpower, which explicitly prohibits gender discrimination in the workplace. The implementation of gender equality at PT. MEC is based on several key factors. First, the company implements an equal wage system between men and women, based on the principle of fairness and efforts to increase the retention of female employees. Second, PT. The MEC implements an inclusive recruitment policy that actively encourages women's participation in various departments, aiming to increase workforce diversity. Third, the company provides facilities and policies that support employee welfare, including maternity leave and adequate lactation facilities. PT. The MEC also takes special measures to ensure the safety of workers, especially women, including anti-harassment policies. However, challenges remain, especially in raising workers' awareness of gender equality rights and encouraging more women to pursue careers in the industry. Although PT. While MECs have demonstrated a strong commitment to gender equality and creating a fair working environment, further efforts are still needed to achieve all-round equality. These findings emphasize the importance of sustainable implementation of more comprehensive policies and strategies in the context of the coal mining industry.